Seed mass, seed production, germination and seedling traits in two phenological types of Bidens pilosa (Asteraceae) - Gurvich, Diego Ezequiel (2004)
Bidens pilosa L. is a summer annual that shows a particular phenological pattern in the Córdoba mountains, Argentina. Some individuals start flowering 1 month after germination (early type), but most of the population starts flowering 4 months after germination (normal type). The aims of this study were to (1) analyse whether differences in flowering phenology affect seed mass and seed production, and (2) assess whether possible differences in seed traits of the two parental phenological types would affect germinability, germination rate, seedling growth and flowering phenology of offspring under laboratory conditions. The study showed that the numbers of seeds per capitulum and per plant were greater in the normal type than in the early type plants. This can be related to plant height, since in the field, normal-type plants are larger than early type plants. However, early type plants produced heavier seeds than normal-type plants. Germination rate was faster in the early type seeds, but total germination was higher in the normal ones. Seedling growth, in terms of height and the date of first flowering, did not differ between the phenological types of parental seed sources. Our results showed that differences in flowering phenology were associated with seed mass and seed production differences. Seed mass appears to be related to germination characteristics but not to seedling growth nor to flowering phenology of offspring.